Chitosan modification with cellulose - gelatin to remove heavy oil from wastewater - Fundji, Wato Nathan (Vaal University of Technology, 2022)
In this study, Chitosan was modified with cellulose and gelatin for the removal of Cu2+, Fe2+, and Pb2+ from oily wastewater. Membranes were prepared and characterized using Fourier Transform Infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and X - Ray Diffraction (XRD). Their changes and permeabilities were studied and showed that pH values slightly changed. The effects of pH solution and conductivity were investigated. Adsorption study was performed to remove the heavy metals. The results revealed that the highest % removal of Cu2+ was 96.62 (pH = 7.52 and conductivity = -12 mV), of Fe2+ was 97.95 (pH = 6.30 and conductivity = +68 mV) and of Pb2+ was 98.86 (pH = 10.58 and conductivity = -170 mV) for the 12: 2: 2 ratio and for the other ratio, results were quite similar. To analyse the impacts of experimental factors, experiments were developed using Central Composite Design (CCD) based and the Response Surface Methodology (RSM). R2 values were 0.99, 0.99 and 0.98 correspondingly to the analysis of variances of Cu2+, Fe2+, and Pb2+, respectively while using the 12: 2: 2 ratio but for the other ratio, results were almost the same. In interpreting the experimental data, the quadratic models were significant and appropriate. For all models, the variations between experimental and predicted values of % Removal were insignificant. The resulting 3D response surface graphs allowed for a paired investigation of variable influences upon every response model. This study aimed to develop a new chitosan membrane as a film-forming material with a lower acid content and improved mechanical properties in order to remove heavy oil from wastewater.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Chitosan; Heavy oil removal from wastewater; Gelatin; Cellulose; Wastewater oil removal; Compounds; Acetic acid; Organic solvent; Heavy metals; Inorganic composition of oil; Dissertations, Academic -- South Africa.; Water -- Pollution.; Oil pollution of water.; Chitosan -- Biotechnology.